An Examination of the Implementation of Criminal Sanctions in Environmental Protection and Management Legislation - Soraya, Joice; Althafzufar, Muhammad Ansy (Lex Journal: Kajian Hukum & Keadilan, 2024)
This research analyzes the regulation and application of criminal sanctions in Law Number 32 of 2009 concerning Environmental Protection and Management (PPLH Law) as an instrument of environmental law enforcement in Indonesia. By using the normative juridical research method, this research examines the regulation of criminal sanctions in the PPLH Law, its application in environmental cases, and its effectiveness in realizing environmental protection and management. The results show that the PPLH Law has provided a strong legal basis for the application of criminal sanctions. However, in practice, it still faces various obstacles, such as the complexity of proof, the limited capacity of law enforcement, and conflicts of interest. The effectiveness of the application of criminal sanctions is also not optimal because various factors, such as the quality of investigations, inter-agency coordination, and resource support, influence it. This research recommends the improvement of criminal sanction arrangements in the PPLH Law, strengthening law enforcement institutions and resources, increasing community participation, and applying the principle of restorative justice in the settlement of environmental criminal cases. These efforts are expected to strengthen environmental law enforcement and realize sustainable development in Indonesia.